Deteksi Jejak Komponen Polimer Geomembran pada Garam dengan Alas Pengering Plastik Geomembran - Pasaribu, Desi Lusiani; Arnata, I Wayan; Harjosuwono, Bambang Admadi (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2022)
The use of geomembrane plastic in salt production has been effectively used since 2012. Geomembrane plastic can increase the growth of salt production by almost 100%. Geomembrane plastic is a relatively thin, interconnected polymer sheet. Geomembrane plastic is used repeatedly for approximately two years and is exposed to sunlight. This research was conducted to determine the traces of geomembrane polymer components in salt dried in the sun using a geomembrane plastic drying mat. UV-Visible was used to detect the presence of traces of polymer components and determine the functional groups of polymer components using FTIR spectroscopy. The results of the UV-Visible identification of salt water and polluted distilled water showed the presence of two migrating chemical elements and the FTIR identification of the samples showed absorption peaks at 3874-3209 cm?¹ O-H, 3059-2782 cm?¹ C-H, 1709-1509 cm?¹ C=C, 1378 cm?¹ CH and 1224-1068 cm?¹ C-C. The geomembrane plastic molecules that are thought to migrate to the salt are the HDPE copolymer and the antioxidant additive Irganox 1330.